The factors that affect financial distress during the covid-19 pandemic - Nurul Hidayanti; Yuli Tri Cahyono (Proceeding International Conference on Accounting and Finance, 2023)
This research aims to determine the effect of sales growth, profitability, liquidity, and operating cash flow on financial distress during the Covid-19 pandemic. The population in this study are all property, real estate, and construction companies listed on the Indonesia Stock Exchange in 2019-2021. The sampling technique used a purposive sampling method. Samples that meet the criteria are 44 companies with a total of 132 data for three years of observation. Data analysis used logistic regression with the help of SPSS program. The results of the study show that sales growth and profitability have an effect on financial distress, while liquidity and operating cash flow have no effect on financial distress.